Construction of an AuHQ nano-sensitizer for enhanced radiotherapy efficacy through remolding tumor vasculature. Issue 21 (20th May 2021) - Wang, Xiaohui; Niu, Xiaoyan; Zhang, Xiaolei; Zhang, Zhenjie; Gao, Xuefeng; Wang, Wei; Yuan, Zhi
Abstract : An amazing nanoplatform (AuHQ) was utilized to normalize tumor vessels, thereby relieving tumor hypoxia and significantly increasing the accumulation of nanoparticles at a tumor site, which can significantly improve the radiotherapy efficacy. Abstract : As a radiotherapy sensitizer, gold-based nanomaterials can significantly enhance radiotherapy efficacy. However, the severe hypoxia and the low accumulation of nanomedicine at the tumor site caused by poor perfusion have seriously affected the effect of radiotherapy. Tumor vascular normalization has emerged as a new strategy for increasing the efficacy of radiotherapy due to its ability to relieve hypoxia and increase perfusion. However, a commonly used approach of blocking a single growth factor to induce vascular normalization is limited by the compensation effect of evasive drug resistance. In this work, we developed a strategy to simultaneously reduce the expression of multi-angiogenic growth factors by suppressing the oxidative stress effects in tumor. Herein, gold nanoparticles (Au NPs) were modified with 8-hydroxyquinoline (HQ) to obtain AuHQ. This system has a simple structure and could inhibit the production of reactive oxygen species in tumor cells by chelating iron ions, and attenuating the expression of angiopoietin-2, vascular endothelial growth factor and basic fibroblast growth factor in human umbilical vein endothelial cells. In vivo, AuHQ treatment increased pericyte coverage, modulated tumor leakage while alleviating tumor hypoxia and increased blood perfusion, thereby inducing tumor vascular normalization. Consequently, Au accumulation of the AuHQ group increased by 1.94 fold compared to that in the control group. Furthermore, the antitumor efficacy of radiotherapy was increased by 38% compared to the Au NPs-treated group. Therefore, AuHQ may be a promising nanomedicine for future cancer treatment.